PEMAHAMAN QALBU PADA HADIS IMAM AL-BUKHARI N0.52 DAN PENGARUHNYA TERHADAP KESEHATAN MENTAL - Zahra Aini Muthmainnah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2024)
The purpose of this study is to find out what impacts make the heart become damaged and subsequently have an impact on mental health, so that one can always maintain their daily activities to stay healthy. The method used in this research is the tahlili method, which reveals the arguments in the Hadith by describing all aspects and meanings of these arguments according to the expertise and tendencies of the interpreter. The results show that a healthy heart is a heart that is free from everything other than Allah, such as shirk in its various forms. Worship, desire, love, trust, submission of affairs, solemnity, fear, hope, and deeds, are all sincere for the sake of Allah. This healthy heart will cause a person's overall mental health to be good and not experience physical problems. In accordance with the previous conclusions, the author suggests that the study of the influence of the heart on the health of a person's mental health should be continued.